2023
DOI: 10.3390/app13042100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Different Packaging Materials on the Quality Attributes of the Tomato Fruit

Abstract: Post-harvest loss continues to be a significant problem in the food industry. Different packaging materials, designed to reduce fruit damage, are anticipated for various applications in the supply chain. Recently, stamped paper (SP) and expandable polystyrene (EPS) trays have been introduced as tomato retail packaging. Although the combination of paper trays and clear plastic are still not 100% biodegradable packaging, they are promising alternatives to the heavy utilisation of petrochemical-based polymers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The increase in pH values recorded from the three storage containers was in agreement with the findings of Adhikari et al (2020) who revealed that the pH value of tomatoes increases with the storage time due to ripening and respiration. Dladla and Workneh (2023) revealed that unpackaged (control) tomatoes had the highest increase in pH value from 4.20 to 4.60 under ambient storage conditions. Islam et al (2013) also reported an increase in pH of tomato fruits with maturity and mango fruits during storage, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The increase in pH values recorded from the three storage containers was in agreement with the findings of Adhikari et al (2020) who revealed that the pH value of tomatoes increases with the storage time due to ripening and respiration. Dladla and Workneh (2023) revealed that unpackaged (control) tomatoes had the highest increase in pH value from 4.20 to 4.60 under ambient storage conditions. Islam et al (2013) also reported an increase in pH of tomato fruits with maturity and mango fruits during storage, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…P acutifolius genotypes tested in our study presented higher values of total glucose. Glucose represents a significant source of metabolic energy for seedling development, in the formation of nutrients and bioactive compounds contained in the seed [72,73], and these compounds are also mainly bound to sugar molecules (glycosylated residues) and proteins [74].…”
Section: Discussionmentioning
confidence: 99%
“…Many film types are used for food packaging depending on their characteristics. Nylon exhibits good properties as an oxygen, odor and flavor barrier with mechanical strength and high-temperature performance but has a very poor water vapor barrier [5]. Polypropylene (PP) is a non-biodegradable addition to the propylene polymer, and the resins used are mainly isotactic.…”
Section: Introductionmentioning
confidence: 99%
“…Figure5 Sensory quality in seasoned fried mushroom products in 3 packaging formats stored at room temperature for 90 days.…”
mentioning
confidence: 99%